An index and abstracts of Masters dissertations and theses in the fa culties of Commerce, Technology and Veterinary Medicine since 1970 - Tumusiime, Marcial (Kampala: Makerere University, 1997)
Dissertation (BLIS) - Makerere University, 1997
Includes index
Keywords: Dissertations, Academic -- Abstracts; Technology -- Abstracting and indexing; Veterinary Medicine -- Abstracting and indexing; Commerce -- Abstracting and indexing